Integration Of Digital Technology In Mathematics Learning - Yusri Wahyuni; Jamaris; Solfema (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to describe the role of digital technology integration in learning mathematics. The integration study is viewed from the perspective of mathematics learning. It was concluded that the basic principle in integrating digital technology in mathematics learning is that the use of technology does not result in poor conceptual understanding or replaces the role of students' intuition in mathematics, but technology aims to improve students' conceptual understanding and develop students' intuitive abilities in mathematics. Mathematics is divided into two categories, namely knowing mathematics and doing mathematics. Knowing mathematics is related to knowledge of mathematics as a form of knowledge. Meanwhile, doing mathematics is related to mathematical activities